Talent identification and development strategies in elite women`s soccer: a pan-European perspective - McEwan, G. P.; Unnithan, V. B.; Carter, M.; Dugdale, J. H.; Datson, N. (Science and Medicine in Football, 2026)
The question of how best to identify and develop youth soccer players has received considerable attention from the scientific community. Existing literature has, however, largely focused on male players, with comparatively little exploration of the specific approaches employed within women`s soccer. Accordingly, we sought to investigate the key factors deemed important by elite women`s soccer clubs concerning the: 1) identification of potential talent; 2) development of players within the player pathway; and 3) selection of players for the next age group or senior team. Data were generated through semi-structured interviews with 11 key representatives from seven elite women`s soccer clubs. Clubs were purposefully sampled to include the highest performing teams (38 domestic titles and 10 UEFA Women`s Champions League titles) from five European nations (Spain, France, Sweden, Germany, and Italy). Data were analysed using thematic content analysis, resulting in six higher-order themes: 1) prioritising local talent; 2) recruitment from mixed grassroots leagues; 3) creating challenging developmental environments; 4) ensuring player wellbeing; 5) patience in decision-making; and 6) facilitating the youth-to-senior transition through a top-down approach. A total of 17 lower-order themes were subsequently identified. The present study offers novel insights of key strategies deemed important by some of the most successful women`s clubs in top-performing European nations. Future research examining the efficacy of such approaches could help inform the development of evidence-based practices for nurturing the next generation of elite female players.